2016
DOI: 10.1002/acr.22709
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐Utility and Cost‐Effectiveness Analyses of Face‐to‐Face Versus Telephone‐Based Nonpharmacologic Multidisciplinary Treatments for Patients With Generalized Osteoarthritis

Abstract: Objective. To evaluate, from a societal perspective, the cost utility and cost effectiveness of a nonpharmacologic faceto-face treatment program compared with a telephone-based treatment program for patients with generalized osteoarthritis (GOA).Methods. An economic evaluation was carried out alongside a randomized clinical trial involving 147 patients with GOA. Program costs were estimated from time registrations. One-year medical and nonmedical costs were estimated using cost questionnaires. Quality-adjusted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
(49 reference statements)
1
17
0
Order By: Relevance
“…To our knowledge, there are no other economic evaluations of telephone-based interventions for patients with knee osteoarthritis, hampering comparisons to similar interventions. A recent study assessed the cost-effectiveness of a 6-week multidisciplinary face-to-face treatment program compared with a telephone-based program for patients with osteoarthritis [38]. In this study, all patients received in-depth education about osteoarthritis, pain management, physical activity and diet, with the overall goal to enhance self-management skills [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, there are no other economic evaluations of telephone-based interventions for patients with knee osteoarthritis, hampering comparisons to similar interventions. A recent study assessed the cost-effectiveness of a 6-week multidisciplinary face-to-face treatment program compared with a telephone-based program for patients with osteoarthritis [38]. In this study, all patients received in-depth education about osteoarthritis, pain management, physical activity and diet, with the overall goal to enhance self-management skills [38].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study assessed the cost-effectiveness of a 6-week multidisciplinary face-to-face treatment program compared with a telephone-based program for patients with osteoarthritis [38]. In this study, all patients received in-depth education about osteoarthritis, pain management, physical activity and diet, with the overall goal to enhance self-management skills [38]. Patients in the face-to-face group received six therapeutic groups session (2–4 h each), whereas the telephone group received only two face-to-face group sessions (2–2.5 h each) and four individual telephone contacts (15–30 min each).…”
Section: Discussionmentioning
confidence: 99%
“…The study found that from a societal perspective the face-to-face treatment was more likely to be cost-effective at 1-year follow-up. 38 These results, together with the findings from our current study, suggest that telephone-based care for patients with osteoarthritis may not be a cost-effective management approach. Since many patients with osteoarthritis do not receive recommended treatments via clinical models of care, 13,39 understanding why telephone-based interventions are reported to be as effective as face-to-face interventions but not cost-effective, is an important consideration to inform how best to provide care to this patient group.…”
Section: Comparison With the Literaturementioning
confidence: 45%
“…A more recent high-quality study assessed the cost-effectiveness of a 6-week multidisciplinary face-to-face treatment program compared with a telephone-based program for patients with generalised osteoarthritis. 38 In this study, all patients received in-depth education with the overall goal to enhance self-management skills. 38 Patients in the face-toface group received six therapeutic groups session (2-4 hours each), whereas the telephone group received only two face-to-face group sessions (2-2.5 hours each) and four individual telephone contacts (15-30 mins each).…”
Section: Comparison With the Literaturementioning
confidence: 99%
See 1 more Smart Citation